Public Participation in Environmental Monitoring: Examining the Gap Between Regulatory Ideals and Implementation Realities - Jonathan Alfoni Rafael Aritonang; Darma Sakti Tanjung; Khailila Sadira Ginting Munthe; Karina Aprilia; Sigar P Berutu (Journal Social Civilecial, 2026)
Environmental law enforcement plays a crucial role in ensuring sustainable environmental protection and management in Indonesia. Despite the existence of relatively comprehensive environmental regulations, significant gaps remain between regulatory ideals and implementation realities. This study aims to analyze the factors contributing to the gap between environmental regulation and enforcement, particularly concerning institutional performance, public participation, and legal culture, as well as to examine efforts and solutions to minimize these challenges. The research employs a normative legal research method using statutory, conceptual, and case approaches. Legal materials consist of primary, secondary, and tertiary sources collected through library research and analyzed qualitatively using a juridical-normative approach. The study adopts Lawrence M. Friedman’s Legal System Theory to examine environmental law enforcement through the dimensions of legal substance, legal structure, and legal culture. The findings reveal that although Indonesia has established an extensive environmental governance framework, implementation remains constrained by unclear operational regulations, limited institutional capacity, weak inter-agency coordination, inconsistent sanctions, and low public legal awareness. Public participation mechanisms also tend to remain procedural rather than substantive due to limited access to environmental information and inadequate protection for environmental defenders. To address these issues, comprehensive strategies are required, including strengthening institutional capacity, improving regulatory clarity, enhancing coordination among agencies, expanding transparent public participation mechanisms, and promoting environmental legal awareness within society and business sectors. Ultimately, effective environmental governance requires collaborative synergy between the government, private actors, and communities to ensure sustainable environmental protection and legal accountability.